Drugs quality control (Theoretical foundation and practical application) The Coursebook - Pleteneva, T. V.; Morozova, M.A; Uspenskaya, E.V; Khatchaturyan, M.A (Open textbook library., 2019)
The Course book presents the basics of drugs quality control in accordance with regulatory documents (pharmacopoeia of Europe, USA, Japan, Russia) and new data from current scientific periodicals, monographs The features of the physical, spectral and chemical quality control of medicines according to the indicators «identification», «tests» and «assay» are described in detail. Part II presents a workbook, which includes questions for the self-control of the material studied and tasks for a laboratory workshop. The Course book contains reference material and samples of pharmacopoeial articles. The Course book is designed for students of the specialty «Pharmacy».